Enhancing Problem-Solving Skills and Motivation through Cooperative Learning - Debache, Ahlam (Journal of Human Sciences, 2016)
In the present paper, the goal set to assist learners in the process of strategically seeking as well as applying information is given a major consideration in the realm of education. the advantage of raising awareness of problem solving skills and encouraging learners to apply them are two main requirements which go hand in hand to increase performance throughout learning, for we noticed that being informed about some pieces of information does not inevitably necessitate its application but an active involvement into cooperative problem-solving activities fosters higher-order thinking skills namely deductive and inductive types of thinking within cooperative learning environment. Cooperative learning and teaching approach is adopted to increase learners’ academic performance in terms of the space left for them to benefit from the positive interdependence which highlights the mutual exchange of learning experiences skills and leads to meaningful and long-term learning. This research reports the importance of taking recourse to cooperative learning as learning and teaching approach which has a generously positive influence on the enhancement of both thinking skills motivation social and collaborative skills.